Gestión del capital de trabajo y su incidencia en la rentabilidad de la empresa Pipa Company Punchana, 2023 - Pacheco Panduro, Pierre Edwer (2024)
The title of the thesis is "Working capital management and its impact on the performance of the company Pipa Company of Punchana, 2023", and its main objective is to examine the relationship between working capital management and the economic performance of the company. mentioned company. A quantitative approach is used and is defined as a study that adopts a descriptive approach, as well as a non-experimental and crosssectional design. Finally, the justification for the research is provided. The research is justified in the search to improve the economic and financial profitability of the company, influencing both internal and external decisions, in order to maintain favorable results. The technique used was the survey, using a questionnaire as a research instrument. The population and sample consisted of 10 workers. The results indicate that the company has adequate management of working capital, thanks to the efficient management of its financial resources by the owner, standing out in inventory management. It is concluded that the effective management of economic and financial stability depends largely on the vitality of the working capital of Pipa Company EIRL.